2014
DOI: 10.1063/1.4869277
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and spin moments of 5 to 11 nm Fe3O4 nanoparticles measured via x-ray magnetic circular dichroism

Abstract: The orbital and spin contributions to the magnetic moment of Fe in Fe3O4 nanoparticles were measured using X-ray magnetic circular dichroism (XMCD). Nanoparticles of different sizes, ranging from 5 to 11 nm, were fabricated via organic methods and their magnetic behavior was characterized by vibrating sample magnetometry (VSM). An XMCD signal was measured for three different samples at 300 K and 80 K. The extracted values for the orbital and spin contributions to the magnetic moment showed a quenching of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The calculated orbital and spin components indicate a m L close to zero for Fe cations (quenching of the orbital moment) in line with those reported in the literature for Co (1−x) Fe (2+x) O 4 48 and Fe 3 O 4 NPs, 48,68 while the values of m S are higher than the m S reported by Moyer 68 On the other hand, for Co ions the orbital and spin components are comparable (but slightly lower) to those reported in the literature for "bulk" CoFe 2 O 4 film. 48 The enhanced total magnetic moment of Fe in CoFe 2 O 4 NPs can be associated with a dominant concentration of Fe cations in the unit cell, as also observed by Moyer et al, 48 who showed an increase of Fe magnetic moments with increasing x in Co (1−x) Fe (2+x) O 4 structure.…”
Section: Articlesupporting
confidence: 89%
“…The calculated orbital and spin components indicate a m L close to zero for Fe cations (quenching of the orbital moment) in line with those reported in the literature for Co (1−x) Fe (2+x) O 4 48 and Fe 3 O 4 NPs, 48,68 while the values of m S are higher than the m S reported by Moyer 68 On the other hand, for Co ions the orbital and spin components are comparable (but slightly lower) to those reported in the literature for "bulk" CoFe 2 O 4 film. 48 The enhanced total magnetic moment of Fe in CoFe 2 O 4 NPs can be associated with a dominant concentration of Fe cations in the unit cell, as also observed by Moyer et al, 48 who showed an increase of Fe magnetic moments with increasing x in Co (1−x) Fe (2+x) O 4 structure.…”
Section: Articlesupporting
confidence: 89%
“…Based on previous crystallographic studies of these samples [12], the cubic lattice parameter is 8.35 Å and the atomic density is about 13.7 Fe 3 O 4 units per nm 3 . Accounting for combined spins carried by the Fe 2+ and Fe 3+ ions in the spinel structure [18], the saturated magnetization density is about 55 µ B /nm 3 . Assuming a spherical NP shape with a radius of 2.6 nm, we have M s = 4000 µ B .…”
Section: Nm Nanoparticles: Tem and Magnetometrymentioning
confidence: 99%
“…Among others, these behaviors include the precise manner in which the the blocking transition proceeds throughout the sample, and how this affects experimental data [11]; the influence of the structure and morphology across varying length scales [7,12]; and even the estimation of microscopic parameters such as the nanoparticle spin flip activation energy and fluctuation time [13]. There is increasing recognition that a more complete understanding is most likely to be obtained by attacking the problem with a variety of complementary techniques, such as magnetometry [9], Mössbauer spectroscopy [14], electronic microscopy [15] and holography [16], neutron scattering [17], x-ray magnetic spectroscopy [18], or x-ray magnetic scattering [19]. In this context, probes of local magnetism-i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Fe3O4 carries a strong magnetization, supported by the spins of two ions, Fe 2+ and Fe 3+ , distributed ferrimagnetically throughout a spinel crystallographic structure [13,14]. Nano-sized Fe3O4 particles exhibit a strong bulk-like magnetic moment throughout the core of the particle with limited oxidation effects at the surface [15][16][17]. When their size is below about 100 nm, Fe3O4 particles are usually magnetically monodomain, thus forming a single giant magnetic moment, or "nanospin" [18,19].…”
Section: Introductionmentioning
confidence: 99%